Status and Relative Abundance of Alabama Shad, Alosa alabamae, in Alabama - Steven J Rider; Travis R Powell; Jason E Dattilo; Gregory T Miles (Southeastern Fishes Council Proceedings, 2021)
Alabama Shad, Alosa alabamae, an anadromous fish found historically from the Mississippi River basin eastward to the Suwanee River, has experienced population declines and even extirpation in some States. In Alabama, A. alabamae have been found in rivers of the Mobile River basin and Conecuh, Yellow, and Choctawhatchee rivers in the coastal Gulf Plain. We report on our directed and targeted efforts to assess the current status and relative abundance of A. alabamae in Alabama and compare our results to past A. alabamae surveys in Alabama. We completed 52 sampling trips and expended 129.5 hours of boat-electrofishing effort targeting A. alabamae. Sampling was conducted during the spring to coincide with the spring-spawning migration at historical sites and sites conducive for the collection of A. alabamae. No A. alabamae was collected from the Mobile River basin (i.e., Alabama and Tombigbee rivers) and only one A. alabamae was collected from the Conecuh River. We collected seven A. alabamae in 2011 and three in 2018 from the Choctawhatchee River. For the Choctawhatchee River population, our results indicated a precipitous decline in abundance by 71% and 98% from 1999/2000 to 2011 and 2018, respectively. In addition, our results support the extirpation of A. alabamae from the Mobile River basin and a severely depressed population in the Conecuh River. Although A. alabamae was recently denied listing under the Endangered Species Act by the National Marine Fisheries Service due to lack of apparent range-wide extinction, our results indicate what was once considered the second largest population of A. alabamae from the Choctawhatchee River is on the verge of extirpation. Alosa alabamae could become extirpated from Alabama in the near future, which is a significant portion of its range.
Keywords: Mobile River basin; Clupeidae; coastal rivers; extirpation